Nanoengineered Copper: Revolutionizing Breast Cancer Care - Soumitra Mandal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Breast cancer continues to rank as a predominant cause of illness and death among women globally, emphasizing the critical need for innovative and effective treatment approaches. Traditional methods such as chemotherapy, surgery, and radiation therapy often face limitations, including toxicity, resistance, and non-specific targeting. In recent years, advancements in nanotechnology have brought about transformative solutions, with nanoengineered copper emerging as a frontrunner. Nanoengineered copper’s unique properties- including its catalytic capabilities, biocompatibility, and potential for surface modification- offer unprecedented opportunities to revolutionize breast cancer care. These nanoparticles not only enable precise targeting of cancer cells but also improve diagnostic accuracy through advanced imaging techniques. Furthermore, their application in photothermal and photodynamic therapies provides a dual approach to destroying cancer cells while minimizing harm to healthy tissues. With the ability to modulate the tumor microenvironment and act as a platform for combination therapies, nanoengineered copper holds immense promise for both early detection and effective treatment. This article explores the wide-ranging applications of nanoengineered copper, from diagnostic innovations to therapeutic breakthroughs, underscoring its potential to redefine breast cancer management and improve patient outcomes.
Keywords: Nanoparticles in Oncology; Nanoengineered Copper; Breast Cancer Therapy; Photothermal and Photodynamic Therapy; Targeted Drug Delivery